Comparative analysis of the sustainability and seismic performance of a social interest house using RC moment frames and bahareque as structural systems - Tello-Ayala, Ken; Garcia-Troncoso, Natividad; Silva, Christian E.; Zúñiga-Olvera, Carlos; Narvaez-Moran, Julio; Malaga-Chuquitaype, Christian; Mouka, Theodora (Frontiers in Built Environment, 2023)
This study compares the seismic performance and environmental impact of a social housing structure, designed with reinforced concrete, with a structure using guadua angustifolia ’Kunth’ cane. The aim is to contrast the implementation of an ecological material such as the guadua cane, which is an accessible alternative due to its cost and construction time, versus the traditional reinforced concrete (RC) construction method. Both applied to social housing structures. The seismic performance of both methods is analyzed through nonlinear static analysis (pushover) with the objective of establishing the performance; structural and non-structural damage, performance point, maximum displacements, structural elements that induce structural failure, and acting forces, against a design earthquake (established by the NEC DS 2015 Standard), with a return period of 475 years. The environmental impact is evaluated through life cycle analysis of the structure (LCA). Thus, the embodied carbon obtained from each structural element (foundations, beams, columns, floors and roof support elements) was determined, considering the material manufacturing, transportation, and construction. The results obtained demonstrated a higher seismic performance, with a 70% less environmental impact of the guadua cane structure.